2008
DOI: 10.1038/npp.2008.2
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Increases Amygdala Reactivity in Middle-Aged Women to a Young Adulthood Level

Abstract: Testosterone modulates mood and sexual function in women. However, androgen levels decline with age, which may relate to the ageassociated change in sexual functioning and the prevalence of mood and anxiety disorders. These effects of testosterone are potentially mediated by the amygdala. In the present study, we investigated whether the age-related decline in androgen levels is associated with reduced amygdala activity, and whether exogenous testosterone can restore amygdala activity. Healthy young and middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(54 citation statements)
references
References 66 publications
5
49
0
Order By: Relevance
“…These findings parallel evidence in women in which a single administration of T increases amygdala and hypothalamic reactivity to angry facial expressions (19)(20)(21). Notably, these subcortical brain structures are rich in both androgen and estrogen receptors (22)(23)(24) and play a key role in potentiating reactive aggression in animal models (1,25).…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…These findings parallel evidence in women in which a single administration of T increases amygdala and hypothalamic reactivity to angry facial expressions (19)(20)(21). Notably, these subcortical brain structures are rich in both androgen and estrogen receptors (22)(23)(24) and play a key role in potentiating reactive aggression in animal models (1,25).…”
Section: Introductionsupporting
confidence: 67%
“…One hour after drug administration, the phlebotomist drew a second blood draw. Although effects of T on aggressive behavior may be secondary to mood effects, previous studies have failed to document effects of acute T supplementation on subjective mood ratings (18,20), and thus, participants did not complete mood measures after drug administration. Participants then completed a 10-minute session of the Point Subtraction Aggression Paradigm (PSAP; see below), which was used to assay aggressiveness, completed a post-PSAP questionnaire and, then provided a third blood sample.…”
Section: Methodsmentioning
confidence: 96%
“…Derntl et al [9] found a significant positive correlation in healthy men between endogenous testosterone and amygdala response to fearful and angry facial expressions, but no correlation with non-threatening expressions such as sadness and happiness. Similar findings have been reported in healthy women whose endogenous testosterone levels correlated positively with amygdala activity during the processing of fearful and angry faces [10]. Stanton et al [11] found that endogenous testosterone levels were negatively correlated with amygdala BOLD activity and positively correlated with ventromedial prefrontal cortex BOLD activity during the processing of angry faces; however, both findings occurred only in healthy males.…”
Section: Introductionmentioning
confidence: 49%
“…Stanton et al [11] found that endogenous testosterone levels were negatively correlated with amygdala BOLD activity and positively correlated with ventromedial prefrontal cortex BOLD activity during the processing of angry faces; however, both findings occurred only in healthy males. When middle-aged women were given a single dose of testosterone, Van Wingen et al [10] reported positive correlations between exogenous testosterone and activity in the amygdala and superior frontal cortex along with a negative correlation between exogenous testosterone and neural activity in the orbitofrontal cortex and occipital gyrus in response to angry and fearful facial stimuli. Another study reported a significant increase in neural activity in the amygdala and hypothalamus while viewing angry faces after healthy female participants received a .5 ml dose of testosterone [12].…”
Section: Introductionmentioning
confidence: 96%
“…One structure that appears particularly sensitive to T is the amygdala-a region rich in androgen receptors (Rubinaw & Schmidt, 1996), and which functions to promote vigilance and arousal (Davis & Whalen, 2001). For instance, van Wingen et al (2009) found that among healthy young women, endogenous levels of T were positively associated with amygdala activation, and for middle-aged women-with naturally lower levels of T-an administration of exogenous T rapidly increased amygdala reactivity to a level comparable to other women with naturally higher levels of circulating T. A separate study by Hermans et al (2008) indicated that administration of exogenous T to healthy young women enhanced responsiveness to social threat (as indicated by angry facial expressions) in the amygdala, as well as the hypothalamus and orbitofrontal cortex. This latter finding has been conceptually replicated and extended in males, where Goetz and colleagues (2014) found that a single administration of T to healthy young men rapidly (within 90 minutes) increased amygdala, hypothalamic, and periaqueductal grey reactivity to angry facial expressions.…”
Section: Testosteronementioning
confidence: 99%